2009
DOI: 10.1111/j.1741-4520.2009.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical exploration of a dicephalous goat kid using sheet plastination (E12)

Abstract: A dicephalous, 1-day-old, female goat kid was presented for anatomical study. Epoxy plastination slices (E12) were used successfully to explore this condition. They provided excellent anatomic and bone detail, demonstrating organ position, shared structures, and vascular anatomy. Sheet plastination (E12) was used as an optimal method to clarify how the two heads were united, especially the neuroanatomy. The plastinated transparent slices allowed detailed study of the anatomical structures, in a non-collapsed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…If sections 1.5–4.0 mm thick are desired, the piece is frozen at a very low temperature (generally −80°C) and then cut. The individual sections are then plastinated (Fritsch, ; Cook, ; Sora et al, , , , , ; Zhang and Lee, ; Leaper et al, ; Nash et al, , ; Sora and Genser‐Strobl, ; Fritsch et al, ; Al‐Ali et al, ; Elnady and Sora, ; Chen et al, ; Wegmann et al, ; Arredondo et al, ; Liu et al, ; Konschake and Fritsch, ; Liang et al, , ; Bernal‐Mañas et al, ; Thorpe Lowis et al, ; Ottone et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…If sections 1.5–4.0 mm thick are desired, the piece is frozen at a very low temperature (generally −80°C) and then cut. The individual sections are then plastinated (Fritsch, ; Cook, ; Sora et al, , , , , ; Zhang and Lee, ; Leaper et al, ; Nash et al, , ; Sora and Genser‐Strobl, ; Fritsch et al, ; Al‐Ali et al, ; Elnady and Sora, ; Chen et al, ; Wegmann et al, ; Arredondo et al, ; Liu et al, ; Konschake and Fritsch, ; Liang et al, , ; Bernal‐Mañas et al, ; Thorpe Lowis et al, ; Ottone et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The tissue loss during cutting is related to the thickness of the saw blade. Several authors have reported various levels of tissue loss during cutting: 0.4 mm (Sora et al, , , , ; Sora and Genser‐Strobl, ; Sora, ), 0.5 mm (Cook, ), 1 mm (Sora et al , ; Elnady and Sora, ), 1.6 mm (Nash et al , ); and 2 mm (Zhang and Lee, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations